LEVEL OF SATISFACTION AMONG PATIENTS WEARING MAXILLARY COMPLETE DENTURE - Dr Waheed Murad; Dr Uzma Bashir; Dr Naveed Ahmed Memon; Dr Farina Qureshi; Dr Sana Javed; Dr Mahrukh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To compare level of satisfaction among patients wearing maxillary complete denture using closed and open mouth impression.Methodology: Seventy patients with endetulism were selected and divided in two equal groups, group A had maxillary complete denture using closed mouth impression while group B had maxillary complete denture using open mouth impression. Level of satisfaction was assessed between both groups.Results: It was notable that 24 (68.6%) patients in group A were very satisfied with denture comfort, while 12 (34.3%) in group B were moderately satisfied. (P = 0.01). Speech satisfaction was similar between groups (P = 0.39). Despite no notable difference in mastication satisfaction, 26 (74.3%) patients in group B were very satisfied with its efficiency, whereas 13 (37.1%) in group A were moderately satisfied (P = 0.06). A notable difference was found between 28 (80%) patients in group A and 18 (51.4%) in group B in denture retention satisfaction (P = 0.03). Denture satisfaction was similar in both groups.Conclusion: Maxillary full dentures created with closed mouth impression technique are better than open mouth approach for comfort, denture retention, and speech quality, but overall satisfaction was not different.